Políticas públicas para a juventude: a participação do jovem em sua construção - Gomes, Lucilene Felipe (2012)
This research represented an effort of understanding of Brazilian youth and how the society and the public authorities have positioning itself vis-à-vis their issues. His analysis was done from a democratic conception of public policies, seized as forms of the-State realize the significant action of social change, allocating resources, favouring social intervention instruments in the country and on their operation, from a position of clear defence of youngsters as subjects of law. In this study we have seen that, in the country, we don't have a public policy for youth, which led us to carry out an analysis of the process of building this policy and a study about the programs and projects that are being implemented for the juvenile population. The methodology used in the first moment was the desk research and, in the second the qualitative research, through the questionnaire applied and of the interviews used. The results of the 2nd National Conference for Youth pointed to the need for adoption of the Statute and of the national plan for youth, regulating the rights of this population. It was noted that there are several issues to lead the Brazilian State's attention to the problems faced by youth. Throughout this study, it has become necessary to understand public policies that are in line with the economic system, leaving a clear relevance to build and deploy public policies that meet the young in their entirety. Public policies configure themselves as one of the biggest problems for the rulers in this day and age. Despite its irrefutable importance and necessity of customer service policies, the "adult" world presents difficulties in coping with the demands and demonstrations of youth